Some Instances of Ic1/Ic5 Interaction in Post-Tonal Music (and Their Tonnetz Representations) - Stephen C. Brown (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
Drawing on the author’s Dual Interval Space methodology, this essay uses a Tonnetz model to explore the interaction of interval classes 1 and 5 in pieces by Bartók, Stravinsky, and Webern. The analyses attest to the importance of ic1/ic5 pairing for a significant range of post-tonal music, while illuminating processes and relationships that transcend the standard pitch-class operations. In addition, the analyses demonstrate that a generalized Tonnetz model, freed from its customary associations with voice-leading smoothness, can serve as a compelling means for interpreting post-tonal music. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).